Policies on mental health in the workplace during the COVID-19 pandemic: A scoping review. - David Villarreal-Zegarra; C Mahony Reátegui-Rivera; Iselle Sabastizagal-Vela; Miguel Angel Burgos-Flores; Nieves Alejandra Cama-Ttito; Jaime Rosales-Rimache (PLoS ONE)
Background The COVID-19 pandemic has had a profound impact on both mental health and working conditions. Workplaces are conducive spaces for implementing strategies and interventions to promote mental health. In addition to this, they are preventing, identifying, and managing mental disorders effectively. Although international agencies have identified some guidelines for the management of mental health in the workplace in the context of the COVID-19 pandemic, a more precise characterization of both the components of the policies, their implementation, and evidence of the outcome is required to provide useful information for decision-makers. Objectives This study aims to synthesize scientific information regarding national and local policies focusing on preventing or improving, directly or indirectly, mental health problems in the workplace during COVID-19 pandemic. Methods Our study is a scoping review. The Scopus, Web of Science, and Embase databases and PubMed search engine were used. Original and reviewed articles published from January 1, 2020 to October 14, 2021 were included in the research. Articles with abstract or full text in English, Spanish, German and Portuguese were also included. Our strategy is based on identifying policies (intervention) which focuses on directly or indirectly preventing or ameliorating mental health problems in the workplace during COVID-19 pandemic (participants). Results A total of 6,522 records were identified, and only four studies were included in the scoping review, which were of low quality. That is, we found limited evidence evaluating mental health policies using primary or secondary data (empirical evaluation). Among the policies that have been identified are the increase of mental health resources, the promotion of mental health and self-care support programs, and the reduction of barriers to access to mental health treatment. Conclusion Our research finds that there is limited evidence available to evaluate national and local policies aimed at directly or indirectly preventing or ameliorating mental health problems at work during COVID-19 pandemic. This forces decision-makers to use different criteria to guide the allocation of resources and budgets. Therefore, there is a need for health intelligence teams in health systems to be able to assess the impact of policies as an important input for decision-makers.